The Interaction between Mathematical Problem-Solving Skills and Mathematical Communication Skills of Junior High School Students: A Qualitative Approach - Hamdani Syaputra; Armiati Armiati; Yulyanti Harisman (Edumatika, 2025)
Mathematical problem-solving skills (MPSS) and mathematical communication skills (MCS) has a very close relationship. Before solving a problem, students should understand the problem first, processing and presenting their answer, which is a MCS. Different from the previous study, this study reveal the relationship and interaction between students’ MPSS and MCS using a qualitative approach. To do this, a case study method is conducted using valid test and interviews. The test consist of three cases: smartphone storage, riddle about number of chickens and the coop, and area of land to be planted with corn. The participants of this study were eighth-grade 18 students from various junior high scholl and region in West Sumatra. Data analysis used is a descriptive analysis of students' test answers and interview results. The results show that there are five of nine interactions between MPSS and MCS: solver, self-solver, sharer, regular, and receiver. Solver is a student with high MPSS and MCS (2 students), self solver is a student with high MPSS but moderate MCS (6 students), sharer is a student with moderate MPSS but high MCS (4 students), regular is a student with moderate MPSS and MCS (3 students), and receiver is a student with low MPSS and MCS (3 students). The results of this study also show that the relationship between MPSS and MCS is very close. Although there are students who have MPSS and MCS that do not match, this is inseparable from the limitations of the research conducted.